العلاقة بين المسئولية الاجتماعية لمنظمات الأعمال وتعظيم الأرباح: وجهة نظر محاسبية - محمد، عبدالرحمن عمر أحمد Mohammed, Abdulrahman Omar Ahmed (الأكاديمية الأمريكية العربية للعلوم والتكنولوجيا, 2017)
The aim of the study was to explore the impact of the social responsibility of business organizations in profit maximizationsin an accounting view. An analytical descriptive approach was used forthe purpose of this paper. Hundred questionnaires were distributed to the study sample. Eighty nine valid questionnaiers were analyzed. Data and hypotheses tests were processed using SPSS Application. The results show that the commitment of business organizatios towards social responsibility has positive impact on the profit maximization. The study encouragesresearchers to investigate this topic more extensively and also encourags administrations and workers together to know about the importance of accounting in handling social responsibility issues in business corporationsthrough active partcipations in workshops and conference dealing with social responsibility.
هدفت الدراسة إلى معرفة أهمية المحاسبة للمسؤولية الاجتماعية في تعظيم الأرباح. ولتحقيق هذا الهدف تم إتباع المنهج الوصفي التحليلي لتوافقه وطبيعة البحث. وتم توزيع (100) استبانة على أفراد المجتمع، وتم الحصول على (89) استبانة مستوفية للشروط، بنسبة استرداد (89%)، ولغرض تحليل البيانات واختبار الفرضيات، تم استخدام برنامج الرزم الإحصائية للدراسات الاجتماعية (SPSS) ومن النتائج التي توصلت إليها الدراسة أن التزام منظمات الأعمال بمسؤوليتها الاجتماعية يعظم من الأرباح بدرجة كبيرة، وقد تأكد من خلال نتائج التحليل الإحصائي، وجود تأثير لدور المحاسبة عن المسؤولية الاجتماعية لمنظمات الأعمال في تعظيم الأرباح. وأوصت الدراسة بإجراء المزيد من الدراسات المستقبلية حول هذا الموضوع، مع حث الإدارت المختلفة والعاملين بأهمية المحاسبة عن المسؤولية الاجتماعية لهذه المنظمات.
Keywords: منظمات الأعمال -- تعظيم الأرباح -- المسئولية الاجتماعية